Comparative evaluation of the influence of television advertisements on children and caries prevalence - Neeta Ghimire; Arathi Rao (Taylor & Francis Group, 2013)
Introduction: Children watch television during most of their free time. They are exposed to advertisers’ messages and are vulnerable to sophisticated advertisements of foods often detrimental to oral and general health. Objectives: To evaluate the influence of television advertisements on children, the relationship with oral health and to analyze the content of those advertisements. Methodology: A questionnaire-based study was performed among 600 schoolchildren of Mangalore, Karnataka, followed by oral examination. Based on the survey, favorite and non-favorite channels and viewing times were analyzed. Advertisements on children's favorite and non-favorite channels were then viewed, analyzed, and compared. Results: Higher caries prevalence was found among children who watched television and asked for more food and soft drinks. Cariogenic food advertisements were popular on children's favorite channels. Conclusion: Television advertisements may strongly influence children's food preferences and eating habits, resulting in higher caries prevalence. Advertisements regarding healthy food, oral hygiene maintenance, prevention of diseases such as caries should be given priority for the benefit of the health of children.